Improving Students Listening Skill by Using Audio Game “Blind Legend Game” at SMA 1 Siluq Ngurai - Diki Suprianto; Widi Syahtia Pane; Godefridus Bali Geroda (Wadah Inovasi Indonesia, 2023)
AbstractBackground:Listening is one of the basic English skill that mus be mastered. Listening is a listen activity where we hear something, be it a speech, a lecture, or an explanation about something from someone else, where we not only hear but also have to listen and understand and then gain new knowledge from what we hear (Tyagi, 2013).Methodology:This research doing by Classroom Action Research method. The subject of this research was XI-MIPA grade of SMA Negeri 1 SILUQ NGURAI 2022/2023 year of academic and consist of 29 students member. The objective of this research was to improve students’ listening skill in English Lesson by using Blind Legend game at XI-MIPA grade of SMA Negeri 1 SILUQ NGURAI. This research was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data is collected through quantitative and qualitative data. The research purpose is to increase students’ ability in listening English by using Blind Legend game. Findings:This research showed result of increasing that happen on students ability in Listening. The students mean score from pretest until post-test cycle 2 was 66,2, 81,3 and 90,1. The students improvement percentage scores who pass the criteria of success >75 also show changes from the pretest only 6 students (20,7%), post-test cycle I up to 26 student (89,7%) and the final result from post-test cycle II that 28 student (96,6%)Conclusion:Based on the pretest down to the second cycle post-test result and the data got by the researcher on the class, Blind Legend games effectively help students to improve listening skill showed by their scores. Especially the students response toward the teaching process using CAR method. It can be said that the students likes Blind Legend game. It proven by their interest to the material in the class, and perform a dialogue and audio listen then understand what the dialogue talk about.Originality:This research can used for references and help student or teacher to understand how improve listening skill using Blind Legend game in teaching and learning process.